Pemberian Insentif dalam Meningkatkan Kinerja Karyawan PT MNC Skyvision - Sahidah, Ahmad; Anwar, Ahmad Kasiful (Attractive : Innovative Education Journal, 2020)
The various companies, organizations, and institutions certainly want to get good employee performance in each of their respective fields. In the maintenance and management of human resources, they must receive more attention. A person's performance was influenced by the level of employee education, motivation and work experience. The aim of this artilce was to describe the assessment and measurement of employee performance, the benefits of employee performance appraisal, and the factors that influence the performance of employees of PT MNC Skyvision (INDOVISION). This research was a descriptive analysis, which was done through collecting data, compiling or it’s grouping, and then interpreting the data. The results showed that the provision of incentives had a contribution to change employee attitudes and behavior towards better performance. Employee performance was a very important role and its meaning in the decision making process in the future such as identification of all organizational program needs, program introduction, training, selection, recruitment, placement, reward systems,and promotions. Keywords: Incentives of Employee, Improving of Employee Performance